Magmatic Processes Associated with Oceanic Crustal Accretion at Slow-spreading Ridges: Evidence from Plagioclase in Mid-ocean Ridge Basalts from the South China Sea. (10th May 2019) - Yang, Fan; Huang, Xiao-Long; Xu, Yi-Gang; He, Peng-Li
Abstract: Magmatic processes associated with oceanic crustal accretion at slow-spreading mid-oceanic ridges are less well understood compared with those at fast-spreading ridges. Zoned plagioclase in the basalts might record these magmatic processes as a result of the very slow intra-crystal diffusion of CaAl–NaSi. Plagioclase phenocrysts in plagioclase-phyric basalt from Hole U1433B of International Ocean Discovery Program (IODP) Expedition 349 in the South China Sea show complex zoning patterns (e.g. normal, reverse, oscillatory and patchy). These samples provide a rare opportunity to determine the magma dynamics associated with oceanic crustal accretion at slow-spreading ridges through time. Igneous lithological units in Hole U1433B consist of a series of massive lava flows at the bottom and a thick succession of small pillow lava flows at the top. Most of the plagioclase phenocrysts in the massive lava show core–rim zonation with high-An cores (An ∼85%; in mole fraction; Pl-A) in equilibrium with melts that are more primitive than their host. Some high-An cores of Pl-A phenocrysts contain melt inclusions and are depleted in La, Ce, Y and Ti, but enriched in Sr and Eu; this is interpreted as resulting from dissolution–crystallization processes during reaction of hot melt with pre-existing plagioclase cumulates. In the pillow lavas, most of the plagioclase phenocrysts show normal core–mantle–rim zonation (Pl-B) with An contents decreasing gradually from the core to the mantle to the rim, suggesting extensive magma mixing and differentiation. Reversely zoned plagioclases (Pl-C) are sparsely present throughout the basalts, but mostly occur in the lower part of the drill hole. The cores of euhedral Pl-C phenocrysts are compositionally comparable with the mantles of Pl-B phenocrysts, suggesting that the evolved magma was recharged by a relatively primitive magma. Melt inclusion-bearing Pl-A phenocrysts occur mainly in the massive lava, but rarely in the pillow lava, whereas Pl-B phenocrysts are present dominantly in the pillow lava, which reflects reducing melt–rock interaction and enhanced magma mixing, recharging and differentiation from the bottom to the top of the hole. In addition, the extensive magma mixing and differentiation recorded by Pl-B phenocrysts in the pillow lava require the existence of a melt lens beneath the mid-ocean ridge. Consistently, the plagioclase phenocrysts in the pillow lava mostly lack melt inclusions, corresponding to very weak melt–rock reactions, which indicates that the magma was transported through plagioclase cumulates by channel flow and requires a higher magma supply to the magma conduit. Therefore, the textural and compositional variations of plagioclase phenocrysts in the samples reflect the changes in magma dynamics of the mid-ocean ridge basalt through time with respect to oceanic crustal accretion at slow-spreading ridges. Overall, the oceanic crustal accretion process is sensitive to the magma supply. In the period between two episodes of extension, owing to a low melt supply the primitive melt percolates through and interacts with the mush zone by porous flow, which produces melt inclusion-bearing high-An plagioclase through dissolution–crystallization processes. At the initial stage of a new episode of extension, the melt infiltrates the mush zone and entrains crystal cargoes including melt inclusion-bearing high-An plagioclase. During the major stage of extension, owing to a relatively high melt supply the melt penetrates the mush zone by channel flow and can pool as melt lenses somewhere beneath the dikes; this forms intermediate plagioclases and the reverse zoning of plagioclases by magma mixing, recharging and differentiation in the melt lens. Such magmatic processes might occur repeatedly during the episodic extension that accompanies oceanic crustal accretion at slow-spreading ridges, which enhances the lateral structural heterogeneity of the oceanic crust.